SIX3 deletions and incomplete penetrance in families affected by holoprosencephaly. (1st August 2017) - Stokes, Bethany; Berger, Seth I.; Hall, Beth A.; Weiss, Karin; Martinez, Ariel F.; Hadley, Donald W.; Murdock, David R.; Ramanathan, Subhadra; Clark, Robin D.; Roessler, Erich; Kruszka, Paul; Muenke, Maximilian
Abstract: Holoprosencephaly (HPE) is failure of the forebrain to divide completely during embryogenesis. Incomplete penetrance has not been reported previously in SIX3 whole gene deletions, which are known to cause HPE. Both chromosomal microarray and whole exome sequencing (WES) were used to evaluate families with inherited HPE. Two families showed inherited deletions that contain SIX3 and were incompletely penetrant for HPE. Using WES, we ruled out parental mosaicism, a SIX3 hypomorph, and clinically significant variants in genes that are known to interact with SIX3 as causes of incomplete penetrance. We demonstrate the importance of molecular cascade testing in families with HPE and we answer important questions about incomplete penetrance.